Adverse systemic reactions of antihistamines: Highlights in sedating effects, cardiotoxicity and drug interactions - (:unkn) unknown (My University, 2005)
Antihistamines are already among the most frequently used pharmaceutical compounds and with the predictable increase of the prevalence of atopic disease, even more patients are expected to use them in future. Though the common belief on their safety has existed since some decades, they, including the over the counter ones, might potentially bear serious side effects. Thus, the following article focuses on the adverse effects of antihistamines by summarizing the current data mainly on central nervous system and cardiovascular side effects. Meanwhile, less common side effects, and important issues like their use in pregnancy and lactation are also included. Updated information is provided on drug interactions and overdose situations along with their management. As a finalstep, pitfalls in choosing suitable antihistamine/s in special circumstances to avoid adverse effects are also covered. © 2005 Bentham Science Publishers Ltd.
Keywords: Antihistamine; Cardiotoxicity; Drowsiness; Sedation; Side effect